2005
DOI: 10.1158/1078-0432.ccr-04-2422
|View full text |Cite
|
Sign up to set email alerts
|

Combined Dendritic Cell Cryotherapy of Tumor Induces Systemic Antimetastatic Immunity

Abstract: Purpose: Cryotherapy of localized prostate, renal, and hepatic primary tumors and metastases is considered a minimally invasive treatment demonstrating a low complication rate in comparison with conventional surgery. The main drawback of cryotherapy is that it has no systemic effect on distant metastases. We investigated whether intratumoral injections of dendritic cells following cryotherapy of local tumors (cryoimmunotherapy) provides an improved approach to cancer treatment, combining local tumor destructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 27 publications
2
63
0
6
Order By: Relevance
“…36 Machlenkin et al showed that cryoablation with immature DC injected intratumorally before cryoablation prolonged survival, induced tumor-specific CD8 C T cell responses, and strongly reduced the number of metastases in the Lewis Lung model and prevented growth of B16 melanoma tumors upon rechallenge. 37 In summary, cryoablation combined with adjuvants is a new highly promising treatment strategy for various types of cancer.…”
Section: E1049802-6mentioning
confidence: 99%
“…36 Machlenkin et al showed that cryoablation with immature DC injected intratumorally before cryoablation prolonged survival, induced tumor-specific CD8 C T cell responses, and strongly reduced the number of metastases in the Lewis Lung model and prevented growth of B16 melanoma tumors upon rechallenge. 37 In summary, cryoablation combined with adjuvants is a new highly promising treatment strategy for various types of cancer.…”
Section: E1049802-6mentioning
confidence: 99%
“…dendritic cell (41), radiofrequency ablation pretreatment and anti-CTLA4 mAb administration (42), and cryoablative pretreatment and i.t. immature dendritic cells (43) resulted in enhanced antitumor immune responses and antitumor effects. The last one is similar to our protocol.…”
Section: Cd8mentioning
confidence: 99%
“…In both cases, purified cells were expanded in vitro with IL-2 and ortho-anti-CD3 and then examined for cytotoxic activity. In vitro cytotoxicity assays were performed as described (25). Briefly, lymphocytes were washed, resuspended in complete medium, and admixed at different ratios with 5,000 [ …”
Section: Methodsmentioning
confidence: 99%